Relationship Between Patients' Level of Knowledge About Caesarean Section Surgery and Pre-Operative Anxiety in The Operating Room Karunia Kasih Hospital - Ryani Susanti; Kusnanto Kusnanto; Achmad Fauzi (Jurnal Ners, 2026)
Cesarean section is the most appropriate alternative to ensure the safety of the mother and fetus, such as in cases of placenta previa, preeclampsia, or abnormal fetal presentation. However, prior to undergoing a cesarean section, some pregnant women experience feelings of fear and anxiety. These feelings are influenced by various factors, including level of knowledge, educational background, support from a partner, economic circumstances, and psychological aspects. Limited understanding of a condition can increase a person's vulnerability to anxiety. Ignorance about medical procedures is often perceived as a threat or pressure, which in turn triggers stress and fear. This situation is often experienced by pregnant women who do not understand the process of childbirth, especially the stages of a cesarean section and its consequences. This increases the risk of anxiety prior to childbirth.This study used a correlational analytical design with a cross-sectional approach. It was conducted in the Operating Room of Karunia Kasih Hospital, Indonesia, from November to December 2025. A total of 48 respondents were selected using total sampling. Data were collected using a combined Hamilton Anxiety Rating Scale (HARS) and State-Trait Anxiety Inventory (STAI) questionnaire to measure the respondents' anxiety levels and a questionnaire on the respondents' level of knowledge that had been adapted to assess the respondents' knowledge of caesarean section. Data analysis included univariate and bivariate analysis using the Chi-square test with a significance level of 0.05.The results showed that 8 respondents (25.8%) of the 31 respondents had low knowledge of preoperative anxiety and did not experience anxiety, while 23 respondents (74.2%) experienced anxiety. Among the 17 respondents with a good level of knowledge about preoperative anxiety, 10 respondents (58.8%) did not experience anxiety, while the other 7 respondents (41.2%) experienced preoperative anxiety. The statistical test results between the level of knowledge and preoperative anxiety obtained a P value of 0.051. Respondents with a good level of knowledge tended not to experience preoperative anxiety about cesarean section.This study shows a significant relationship between knowledge level and preoperative anxiety in cesarean section patients. Insufficient knowledge can exacerbate patients' preoperative anxiety. These findings highlight the importance of effective communication by health workers and also the importance of patients' curiosity to gain more knowledge to reduce preoperative anxiety.